Blood donors' helping behavior is driven by warm glow: More evidence for the blood donor benevolence hypothesis - Ferguson, E.; Taylor, M.; Keatley, David; Flynn, N.; Lawrence, C. (2012)
BACKGROUND: The benevolence hypothesis (both donor and recipient gain) suggests that blood donors, compared to non-blood donors have a general altruistic motivational preference based on warm glow (i.e., "I donate because it makes me feel good"). With objective behavioral economics tests of altruism and warm-glow giving, this paper offers the first direct experimental test of this hypothesis. The prediction that blood donors will be motivated in general by warm glow was compared to predictions from other theoretical models: strong reciprocity and empathy. STUDY DESIGN AND METHODS: Four experiments and one prospective study examined blood donors' and nondonors' motivations for general charitable giving and blood donation. Variants of the dictator game (DG; a charity DG [CDG] and a warm-glow version of a CDG) were used to provide objective measures of altruism. RESULTS: Blood donors gave less than nondonors on the CDG, but gave more on the warm-glow version. Blood donors' actual donations (in the CDGs and blood donation) were associated with feelings of warm glow. There was no evidence that blood donors were motivated by strong reciprocity or empathic concerns. CONCLUSIONS: This paper offers objective behavioral evidence that blood donors' charitable giving and blood donation, compared to non-blood donors, is more strongly motivated by warm glow. This provides additional support for the benevolence hypothesis of blood donation. © 2012 American Association of Blood Banks.